Algebra Examples
f(x)=-8x-7f(x)=−8x−7
Step 1
Step 1.1
To find the x-intercept(s), substitute in 00 for yy and solve for xx.
0=-8x-70=−8x−7
Step 1.2
Solve the equation.
Step 1.2.1
Rewrite the equation as -8x-7=0−8x−7=0.
-8x-7=0−8x−7=0
Step 1.2.2
Add 77 to both sides of the equation.
-8x=7−8x=7
Step 1.2.3
Divide each term in -8x=7−8x=7 by -8−8 and simplify.
Step 1.2.3.1
Divide each term in -8x=7−8x=7 by -8−8.
-8x-8=7-8−8x−8=7−8
Step 1.2.3.2
Simplify the left side.
Step 1.2.3.2.1
Cancel the common factor of -8−8.
Step 1.2.3.2.1.1
Cancel the common factor.
-8x-8=7-8
Step 1.2.3.2.1.2
Divide x by 1.
x=7-8
x=7-8
x=7-8
Step 1.2.3.3
Simplify the right side.
Step 1.2.3.3.1
Move the negative in front of the fraction.
x=-78
x=-78
x=-78
x=-78
Step 1.3
x-intercept(s) in point form.
x-intercept(s): (-78,0)
x-intercept(s): (-78,0)
Step 2
Step 2.1
To find the y-intercept(s), substitute in 0 for x and solve for y.
y=-8⋅0-7
Step 2.2
Solve the equation.
Step 2.2.1
Remove parentheses.
y=-8⋅0-7
Step 2.2.2
Simplify -8⋅0-7.
Step 2.2.2.1
Multiply -8 by 0.
y=0-7
Step 2.2.2.2
Subtract 7 from 0.
y=-7
y=-7
y=-7
Step 2.3
y-intercept(s) in point form.
y-intercept(s): (0,-7)
y-intercept(s): (0,-7)
Step 3
List the intersections.
x-intercept(s): (-78,0)
y-intercept(s): (0,-7)
Step 4